2016
DOI: 10.4172/1920-4159.1000220
|View full text |Cite
|
Sign up to set email alerts
|

Utilization Assessment of Surgical Antibiotic Prophylaxis at Ayder Referral Hospital, Northern Ethiopia

Abstract: Introduction: Surgical site infection represents a significant burden in terms of patients' morbidity, mortality and hospital costs which can be prevented using prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
16
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 20 publications
8
16
3
Order By: Relevance
“…However, overall adherence to all aspects of the guideline occurred in only 28% 11 . Many other studies conducted in multiple countries did report similar results 10,13,17 . The results from multivariable logistic regression analysis showed that several factors emerged as being significantly associated with the appropriateness of antibiotic choice and duration of antibiotic prophylactic administration.…”
Section: Discussionsupporting
confidence: 55%
“…However, overall adherence to all aspects of the guideline occurred in only 28% 11 . Many other studies conducted in multiple countries did report similar results 10,13,17 . The results from multivariable logistic regression analysis showed that several factors emerged as being significantly associated with the appropriateness of antibiotic choice and duration of antibiotic prophylactic administration.…”
Section: Discussionsupporting
confidence: 55%
“…Data abstraction format was prepared based on previously published studies [ 7 , 9 , 10 ]. It was pretested on 15 patients, modified accordingly and used for data collection.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies of antibiotic prophylaxis usage have shown wide variation in compliance to guidelines [ 6 ]. Selection, timing and duration of antimicrobial prophylaxis use showed high noncompliance whereas indication and dose were relatively more satisfactory parameters [ 6 , 7 ]. The variation in practice across different setups could be attributed to the variation in the published guidelines, the lack of acceptance of the guideline among the surgeons, and the lack of awareness and availability of the guideline to service delivering professionals or setups [ 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SSIs usually occur at or near the incision area within 30 or 90 days, depending upon the procedure performed. SSIs are often localized to the incision site but can also extend into deeper adjacent structures [2].…”
Section: Introductionmentioning
confidence: 99%